2012
DOI: 10.1111/j.1755-263x.2012.00306.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing exposure to extreme climatic events for terrestrial mammals

Abstract: There is robust evidence that climate change will modify the frequency and intensity of extreme climatic events. The consequences for terrestrial biota may be dramatic, but are yet to be elucidated. The well-established IUCN Red List does not, for example, include any explicit quantification of the current level of exposure to extreme climatic events in any species-based risk assessment. Using globally distributed data for cyclones and droughts as well as information on the distribution of 5,760 terrestrial ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 45 publications
0
49
0
Order By: Relevance
“…Of the three components of vulnerability, our ability to measure exposure to extreme events is arguably the most advanced. For example, over 30% of threatened terrestrial mammals have experienced significant exposure to cyclones, droughts or a combination of both (Ameca y Juárez, Mace, Cowlishaw, Cornforth, & Pettorelli, ). Measurements of exposure should not, however, rely solely on historical patterns of extreme events.…”
Section: Discussionmentioning
confidence: 99%
“…Of the three components of vulnerability, our ability to measure exposure to extreme events is arguably the most advanced. For example, over 30% of threatened terrestrial mammals have experienced significant exposure to cyclones, droughts or a combination of both (Ameca y Juárez, Mace, Cowlishaw, Cornforth, & Pettorelli, ). Measurements of exposure should not, however, rely solely on historical patterns of extreme events.…”
Section: Discussionmentioning
confidence: 99%
“…That percentage is even higher for endemic mammals; almost all endemic species are predicted to be exposed in more than 80% of their range. The ability to identify populations at higher risk is paramount to implement proactive on-the-ground conservation actions, aiming to increase population resilience against negative effects of climate change [23,40]. …”
Section: Discussionmentioning
confidence: 99%
“…) at a time when species already face habitat conversion, degradation and exploitation. This exacerbation of natural disturbance regimes will likely worsen many types of resource bottlenecks (Ameca y Juárez et al ., ) and result in nonlinear effects on biota. Species may be adapted to resource scarcity to a certain extent, or for a given duration, but beyond that point, population recovery may be impossible (Fig.…”
Section: Conceptual Frameworkmentioning
confidence: 97%
“…Some habitats, such as grasslands, return quickly to pre‐disturbance conditions following such disturbances, but others, such as forests and savannas, recover more slowly (Sutherland & Dickman, ; Jones & Schmitz, ; Allen et al ., ; Haslem et al ., ; Williams et al ., ). At the broad scale, a recent review of the overlap between the distribution of terrestrial mammals and land areas exposed to drought and cyclones identified high proportions of mammals exposed to climate extremes across West Africa and Madagascar (Ameca y Juárez et al ., ). While species that occupy habitat prone to already‐high frequencies of these disturbances are generally well adapted to them, increases in the frequency or intensity of such disturbance may nonetheless take these species past tolerance thresholds (Fig.…”
Section: Conceptual Frameworkmentioning
confidence: 99%